Identification of Bacteria Capable of Chromium Bioremediation from the Environment (Plant Tissue Culture and Biotechnology, 2024)
With the increased urbanization and industrial development, the environment is getting polluted severely day by day.  In Bangladesh, the capital city Dhaka is surrounded by a circular river system, most of which are highly polluted due to discharge of municipal and industrial untreated waste water that has been overloaded with different types of toxic heavy metals. Cr (VI) being used in various activities of industries and its improper treatment lead to contamination of the environment. This study aimed to isolate bacteria with chromium bioremediation potential from the environment. A total of 71 bacteria were isolated, of which all grew in the presence of 100 ppm, 93% in 200 ppm, 46% in 400 ppm, 6% in 600 and 4% in 1000 ppm chromium. Fourteen bacteria selected for chromium reduction by Diphenyl Carbazide Assay showed 23-89% reduction. Of these 14 isolates, 5 were tested for biosorption of chromium. Variable sorption of upto 69% was observed. The 16s rDNA of 6 candidate bacteria were sequenced. These isolates were identified as Kurthia gibsonii, Acinetobacter schindleri, Pseudomonas aeruginosa, Exigubacterium sp., Rhodococcus sp., and Bacillus sp. The reduction potential was found to be highest for Bacillus species (78%) and lowest for Kurthia gibsonii (4.8%). This study has successfully identified six potential bacterial candidates for the bioremediation of chromium (VI). Further research into the mechanisms adopted by these bacteria and genetic manipulation will help to formulate a single or mixture of isolates that can efficiently remove hexavalent chromium from polluted water.Plant Tissue Cult. & Biotech. 34(1): 71-81, 2024 (June)